2017
DOI: 10.1186/s11671-017-2241-3
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Properties of Fullerene-Derived Nanomaterials and Their Polymer Composites: Drastic Pumping Out Effect

Abstract: The evolution of paramagnetic properties of the fullerene soot (FS), fullerene black (FB), and their polymer composites Phenylon C-2/FS, FB has been studied using the electron paramagnetic resonance (EPR) method. For the first time, a drastic growth of the EPR signals in the FB, FS, and composite samples was observed under pumping out at temperatures T = 20 ÷ 300 °C, which is attributed to the interaction between carbon defects and adsorbed gas molecules, mainly oxygen.It is shown that the ensemble of paramagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The presence of fullerene guests in the cages of ZIF-8 is confirmed additionally by ESR spectroscopy. Off-the-shelf fullerene shows a weak, sharp ESR line with a g -value around g = 2.002 and the peak-to-peak line width around W pp ≈ 0.1 mT, due to defects in the fullerene structure (Figure S21). While pristine ZIF-8 does not show this signal, both ESR investigated C 60 @ZIF-8 (15%) and C 60 @ZIF-8 (100%) exhibit a similar but broader W pp ≈ 0.2 mT fullerene line (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fullerene guests in the cages of ZIF-8 is confirmed additionally by ESR spectroscopy. Off-the-shelf fullerene shows a weak, sharp ESR line with a g -value around g = 2.002 and the peak-to-peak line width around W pp ≈ 0.1 mT, due to defects in the fullerene structure (Figure S21). While pristine ZIF-8 does not show this signal, both ESR investigated C 60 @ZIF-8 (15%) and C 60 @ZIF-8 (100%) exhibit a similar but broader W pp ≈ 0.2 mT fullerene line (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed morphological analysis of fullerene revealed that some of the nanocarbons have fullerene-like structures, suggesting that the growth mechanism of nanocarbon is somewhat similar to that of fullerene. Further, some of the investigators observed fullerene-like soot in the nanocarbon sitting on the surface of aluminosilicate spheres of CFA, justifying that primary fullerene particles are arranged in a chain-like assembly [107]. Such fullerene-like structures shows multi-shelled structures, which are interlinked by evidence of the appearance of strongly bent graphene sheets or ribbons and double shells.…”
Section: Tribo-electrostatic Separation (Tes)mentioning
confidence: 96%
“…However, low wear resistance hinders its widespread use in tribological compounds. It is known from the literature [12,13] that low-and high-modulus CF improve the tribological properties of aliphatic and aromatic polyamides, because of which the developed PCM is actively used in the agricultural, metallurgical and automotive industries instead of serial materials.…”
Section: Introductionmentioning
confidence: 99%